The fourth première of the Human Development Index - Guido Lüchters; Lukas Menkhoff (Intereconomics, 1995)
The United Nations Development Program has published its Human Development Index values for most countries of the world for the past five years. It claims the index provides information that goes beyond the widely-used GDP data and is relevant for policy-making. Critical examination shows that the index does not yet live up to this claim.
Keywords: 330; Development Indicators